Bentuk Masjid Berdasarkan Teknik, Material dan Motif - dharmawan, Cherry dharmawan (Program Studi Desain Interior Unikom, 2015)
The Archicture of Mosque or mesjid word is not implicit in Al Qurâ€™an. Mosque or mesjid has a meaning as pray to Allah with whole hearted.Style and morphology in Architecture Mosque has envolved since century in the whole world, that if it is viewed in more detail, it will show much difference in many region and has own characteristic mosque to each other. The architectural difference of mosque can be describe in three part : paradigm, concept, and the culture of people and time period of the mosque is built.The fuction, symbols, and struktur technology of mosque architecture and as well the using of materials integrally create specified mosque morphology in many region, related to the culture of the people that mosque is built. â€œThe Islamic culture â€œ is â€œDien Islamâ€, that organize the relationship between man and Allah ( habbluminnallah ), and man and man ( habbluminnas ). The â€œDien Islamâ€, create the specified morphology of architecture mosque and become the iconografic islamic architecture.Keyworad : Mosque, Form, Typology